Accountability of Village Apparatus in Village Financial Management in Batuyang Village, Pringgabaya District, East Lombok Regency - Iskandar, Renayu Meilda; Inapty, Biana Adha; Isnawati, Isnawati (Formosa Journal of Applied Sciences, 2024)
The aim of the research is to assess the level of accountability shown by village officials in Batuyang Village, Pringgabaya District, East Lombok Regency, especially in terms of financial management. This research uses a qualitative method with a descriptive approach, utilizing interviews and documentation as data collection techniques. Participants in this research consisted of various village officials, including the village head, village secretary, village treasurer, development department, and chairman of the BPD. The findings show that village officials in Batuyang Village have effectively fulfilled their responsibilities in ensuring accountability in financial management. This includes fulfilling their duties in the areas of planning, implementation, administration, reporting, accountability, supervision and guidance, in accordance with the requirements set out in Minister of Home Affairs Regulation No. 113 of 2014.